Comparison of gait biomechanics in patients with and without knee osteoarthritis during different phases of gait - Karia,M; Masjedi,M; Duffell,L; Kotti,M; McGregor,A (Journal of Orthopaedics, Trauma and Rehabilitation, 2018)
Background: This study aimed to characterise knee adduction angles (KAA) and knee adduction moments (KAM) and compare this with foot centre of pressure (COP) in volunteers with and without knee osteoarthritis (OA). Methods: A total of 108 participants were recruited; 84 had no known pathology, 18 had medial knee OA, and six had lateral knee OA. Linear regression was used to determine correlations between the normalised COP, KAM, and KAA during each phase of gait for all participants. Results: The first phase of gait demonstrated significant differences between groups for all measures: KAA in all phases, COP in phases one and two, and KAM in phase one only. Conclusion: The largest mechanical changes are seen in the first phase of gait in osteoarthritic patients. Although COP is an easy to measure tool, it is not as sensitive as KAA and did not demonstrate a significant difference between healthy and medial OA patients.